2002
DOI: 10.1007/s10350-004-6412-9
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Failure Rate of Ileal Pouch-Anal Anastomosis and Quality of Life After Failure

Abstract: The most common cause of pouch failure is fistula, whereas pouch excision is rarely caused by pouchitis. The impaired quality of life of patients in the failure group was caused by impairment of physical function and restrictions in social life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(101 citation statements)
references
References 18 publications
5
93
1
2
Order By: Relevance
“…A isquemia pode ser também lenta e tardia e, neste caso, poderá ocorrer disfuncionalização progressiva com fibrose do RI e até necessidade de remoção do mesmo. LOVEGROVE et al (24) mencionaram 4,5% e LEPISTÖ et al (22) , 5,3% de falência do reservatório por isquemia, próximo ao encontrado neste estudo, de 4,3%. Mesmo assim, em dois dos três casos que evoluíram com isquemia do RI, esta poderia ter sido atribuída a não preservação da arcada do cólon direito, pois foram operados no início da casuística, quando não se realizava esta técnica (13) .…”
unclassified
“…A isquemia pode ser também lenta e tardia e, neste caso, poderá ocorrer disfuncionalização progressiva com fibrose do RI e até necessidade de remoção do mesmo. LOVEGROVE et al (24) mencionaram 4,5% e LEPISTÖ et al (22) , 5,3% de falência do reservatório por isquemia, próximo ao encontrado neste estudo, de 4,3%. Mesmo assim, em dois dos três casos que evoluíram com isquemia do RI, esta poderia ter sido atribuída a não preservação da arcada do cólon direito, pois foram operados no início da casuística, quando não se realizava esta técnica (13) .…”
unclassified
“…When it was first introduced, complication rates of 60-70% and failure rates of up to 30% were reported. The complication rate has decreased dramatically, so overall the failure rate now is less than 5% at large centers [48][49][50]. This is due to modifications in technique as well as increased experience both with the technical aspects of the procedure as well as the management of complications.…”
Section: The Pelvic Pouch Proceduresmentioning
confidence: 98%
“…Lepisto et al [50] reported an overall failure rate of 5.3%. The cumulative probability of pouch failure was 1% at 1 year, 5% at 5 years and 7% at 10 years.…”
Section: Pouch Failurementioning
confidence: 99%
“…2,8,13,14 Failure occurs in 3-15% of patients. [2][3][4][6][7][8]11,[14][15][16] Data from the UK National Pouch Registry, comparing function and failure of 2364 patients undergoing IPAA with those of 127 who required subsequent abdominal salvage surgery, showed that functional results were poorer in the latter, with higher failure rates (7.7 vs 27.5%, p < 0.001). 15 Pouch retention rates after reconstructive surgery range between 0 and 50%.…”
Section: Discussionmentioning
confidence: 99%